Extreme energetic electron fluxes in low Earth orbit: Analysis of POES E > 30, E > 100, and E > 300 keV electrons. Issue 2 (20th February 2016) - Meredith, Nigel P.; Horne, Richard B.; Isles, John D.; Green, Janet C.
Abstract: Energetic electrons are an important space weather hazard. Electrons with energies less than about 100 keV cause surface charging, while higher‐energy electrons can penetrate materials and cause internal charging. In this study we conduct an extreme value analysis of the maximum 3‐hourly flux of E > 30 keV, E > 100 keV, and E > 300 keV electrons in low Earth orbit as a function of L ∗, for geomagnetic field lines that map to the outer radiation belt, using data from the National Oceanic and Atmospheric Administration Polar Operational Environmental Satellites (POES) from July 1998 to June 2014. The 1 in 10 year flux of E > 30 keV electrons shows a general increasing trend with distance ranging from 1.8 × 10 7 cm −2 s −1 sr −1 at L ∗ =3.0 to 6.6 × 10 7 cm −2 s −1 sr −1 at L ∗ =8.0. The 1 in 10 year flux of E > 100 keV electrons peaks at L ∗ =4.5–5.0 at 1.9 × 10 7 cm −2 s −1 sr −1 decreasing to minima of 7.1 × 10 6 and 8.7 × 10 6 cm −2 s −1 sr −1 at L ∗ =3.0 and 8.0, respectively. In contrast to the E > 30 keV electrons, the 1 in 10 year flux of E > 300 keV electrons shows a general decreasing trend with distance, ranging from 2.4 × 10 6 cm −2 s −1 sr −1 at L ∗ =3.0 to 1.2 × 10 5 cm −2 s −1 sr −1 at L ∗ =8.0. Our analysis suggests that there is a limit to the E > 30 keV electrons with an upper bound in the range 5.1 × 10 7 to 8.8 × 10 7 cm −2 s −1 sr −1 . However, the results suggest that there is no upper bound for the E > 100 keV and E > 300 keV electrons. Key Points: We determine the 1 in 10, 1 in 50, and 1 in 100 events for energetic electrons in low Earth orbit The 1 in 10 year flux of E > 30 keV electrons lies in the range 1.8–6.6 ×10 7 cm −2 s −1 sr −1 The E > 30 keV electrons have an upper limit in the range 5.1–8.8 ×10 7 cm −2 s −1 sr −1